'No Evil is Without Good': A Comparative Analysis of Pre‐pack Sales in the UK and the Netherlands. Issue 3 (7th June 2018) - Kastrinou, Alexandra; Vullings, Stef
Abstract: In the last decade or so, the pre‐pack has been widely endorsed as a significant rescue tool across a range of European jurisdictions. Although the seamless prepack can prove to be a very attractive method of affecting a corporate restructuring, a variety concerns nevertheless arise primarily due to the lack of transparency of the process. The aim of this article is to provide an overview of the pre‐pack process in two different jurisdictions commonly regarded as creditor‐friendly, namely, the UK and the Netherlands. In addition, the aim of the article is to offer a comparative analysis of the approach taken in these two jurisdictions towards the pre‐pack, with particular regard placed on the perspective of secured creditors. Copyright © 2018 INSOL International and John Wiley & Sons, Ltd.